Do you pay to go private?: a single centre comparison of induction of labour and caesarean section rates in private versus public patients - Simon Craven; Fionnuala Byrne; Rhona Mahony; Jennifer M. Walsh (BMC, 2020)
Abstract Background The aim of this study was to compare rates of induction and subsequent caesarean delivery among nulliparous women with private versus publicly funded health care at a single institution. This is a retrospective cohort study using the electronic booking and delivery records of nulliparous women with singleton pregnancies who delivered between 2010 and 2015 in an Irish Tertiary Maternity Hospital (approx. 9000 deliveries per annum). Methods Data were extracted from the National Maternity Hospital (NMH), Dublin, Patient Administration System (PAS) on all nulliparous women who delivered a liveborn infant at ≥37 weeks gestation during the 6-year period. At NMH, all women in spontaneous labour are managed according to a standardised intrapartum protocol. Twenty-two thousand two hundred thirty-two women met the inclusion criteria. Of these, 2520 (12.8%) were private patients; the remainder (19,712; 87.2%) were public. Mode of and gestational age at delivery, rates of and indications for induction of labour, rates of pre-labour caesarean section, and maternal and neonatal outcomes were examined. Rates of labour intervention and subsequent maternal and neonatal outcomes were compared between those with and without private health cover. Results Women attending privately were more than twice as likely to have a pre-labour caesarean section (12.7% vs. 6.5%, RR = 2.0, [CI 1.8-2.2])); this finding persisted following adjustment for differences in maternal age and body mass index (BMI) (adjusted relative risk 1.74, [CI 1.5-2.0]). Women with private cover were also more likely to have induction of labour and significantly less likely to labour spontaneously. Women who attended privately were significantly more likely to have an operative vaginal delivery, whether labour commenced spontaneously or was induced. Conclusions These findings demonstrate significant differences in rates of obstetric intervention between those with private and public health cover. This division is unlikely to be explained by differences in clinical risk factors as no significant difference in outcomes following spontaneous onset of labour were noted. Further research is required to determine the roots of the disparity between private and public decision-making. This should focus on the relative contributions of both mothers and maternity care professionals in clinical decision making, and the potential implications of these choices.